Safety at Work : The Limits of Self Regulation - Tucker, Eric (Relations Industrielles / Industrial Relations, 1989)
This article reviews the book, "Safety at Work : The Limits of Self Regulation," by Sandra Dawson, Paul Willman, Martin Bamford & Alain Clinton.